Enterprise Risk Management and Firm Value: The Role of Board Monitoring - Muhammad Faisal; Auliffi Ermian Challen (Association of Certified Fraud Examiners Indonesia Chapter, 2021)
This study aims to obtain empirical evidence related to the influence of Enterprise Risk Management on firm value and the role of monitoring by the Board of Directors and the Board of Commissioners in moderating the effect of ERM on firm value. The sample used is manufacturing companies listed on the Indonesia Stock Exchange in 2014-2017. The test results show that ERM is proven to be able to suppress the uncertainty that arises from the company's activities and the conflicts that occur, which affect the formation of firm value. Furthermore, the excessive number of directors is proven to harm company performance because it is prone to conflicts of interest and the many parties who have the opportunity to become free riders in their responsibilities as directors. So, the board of directors who have an effective role is only carried out by a few people. On the other hand, there are many commissioners in a company that proves to be not very influential in moderating the influence of ERM on the company's value. This research is expected to contribute to the accounting literature in filling the existing gaps, especially regarding Enterprise Risk Management.